Behaviour of Water Droplets Under the Influence of a Uniform Electric Field in Nanocomposite Samples of Epoxy Resin/TiO2 - Bairaktari, Α.; Danikas, M.; Zhao, X.; Cheng, Y.; Zhang, Y. (Engineering, Technology & Applied Science Research, 2013)
In this paper nanocomposite samples of epoxy resin and TiO2 nanoparticles were investigated with water droplets on their surface. A uniform electric field was applied and the behaviour of the water droplets was observed. Parameters that were studied were the water conductivity, the droplet volume, the number of droplets and the droplet positioning with respect to (w.r.t.) the electrodes. All above mentioned parameters influence the flashover voltage of the samples. It is to be noted that – at least in some cases – the water droplet positioning w.r.t. the electrodes was more important in determining the flashover voltage than the droplet volume.